Options for keeping the food system within environmental limits. (25th October 2018) - Springmann, Marco; Clark, Michael; Mason-D'Croz, Daniel; Wiebe, Keith; Bodirsky, Benjamin; Lassaletta, Luis; Vries, Wim; Vermeulen, Sonja; Herrero, Mario; Carlson, Kimberly; Jonell, Malin; Troell, Max; et al.
Abstract The food system is a major driver of climate change, changes in land use, depletion of freshwater resources, and pollution of aquatic and terrestrial ecosystems through excessive nitrogen and phosphorus inputs. Here we show that between 2010 and 2050, as a result of expected changes in population and income levels, the environmental effects of the food system could increase by 50–90% in the absence of technological changes and dedicated mitigation measures, reaching levels that are beyond the planetary boundaries that define a safe operating space for humanity. We analyse several options for reducing the environmental effects of the food system, including dietary changes towards healthier, more plant-based diets, improvements in technologies and management, and reductions in food loss and waste. We find that no single measure is enough to keep these effects within all planetary boundaries simultaneously, and that a synergistic combination of measures will be needed to sufficiently mitigate the projected increase in environmental pressures. A global model finds that the environmental impacts of the food system could increase by 60–90% by 2050, and that dietary changes, improvements in technologies and management, and reductions in food loss and waste will all be needed to mitigate these impacts.